(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to assess the impact of implementing the stages of crisis management systems on the preparedness of healthcare organizations in facing crises. A field study was conducted at King Fahd General Hospital in Jeddah, Kingdom of Saudi Arabia. The researcher adopted a descriptive analytical approach and utilized a questionnaire to collect data from a diverse sample of hospital staff, including medical, nursing, and administrative personnel. The study focused on five key stages of crisis management: early warning detection, preparedness and prevention, damage containment, recovery, and organizational learning. The results revealed a statistically significant impact of each of these stages on the hospital’s level of preparedness. The "recovery" and "damage containment" stages showed the strongest correlation with actual preparedness, whereas the "preparedness and prevention" stage revealed gaps related to the availability of human and technological resources. Additionally, the results indicated statistically significant differences in preparedness assessments based on job categories, with medical staff demonstrating greater awareness of crisis situations compared to administrative staff. The study recommended the development of a comprehensive health crisis management system that ensures integration across all stages, promotes a culture of organizational learning, and activates emergency plans through regular staff training.